2015
DOI: 10.1007/s11606-015-3233-6
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination in Healthcare Settings is Associated with Disability in Older Adults: Health and Retirement Study, 2008–2012

Abstract: BACKGROUNDAs our society ages, improving medical care for an older population will be crucial. Discrimination in healthcare may contribute to substandard experiences with the healthcare system, increasing the burden of poor health in older adults. Few studies have focused on the presence of healthcare discrimination and its effects on older adults.OBJECTIVEWe aimed to examine the relationship between healthcare discrimination and new or worsened disability.DESIGNThis was a longitudinal analysis of data from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
58
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 31 publications
(22 reference statements)
8
58
0
10
Order By: Relevance
“…23,[37][38][39] A prior study utilizing data from HRS examined discrimination in the health care setting in 2008 only. 40 Our finding that reports of discrimination are common, especially for Blacks, is consistent with prior literature. [22][23][24] These results, along with previous findings, highlight the pervasiveness of patient-reported discrimination in the health care setting.…”
Section: Resultssupporting
confidence: 91%
“…23,[37][38][39] A prior study utilizing data from HRS examined discrimination in the health care setting in 2008 only. 40 Our finding that reports of discrimination are common, especially for Blacks, is consistent with prior literature. [22][23][24] These results, along with previous findings, highlight the pervasiveness of patient-reported discrimination in the health care setting.…”
Section: Resultssupporting
confidence: 91%
“…It was recently reported that one of five adults over the age of 50 years experiences discrimination in health care settings (22). In the present study, the blood volume collected decreased with increasing patient age.…”
Section: Discussionsupporting
confidence: 51%
“…One mechanism could be that perceptions of disability discrimination in healthcare settings serve to impede access to health services. An analysis of HRS found that reports of frequent discrimination in healthcare settings were predictive of new or worsened disability over 4-year follow-up 42. Quantitative38 43 and qualitative44 evidence suggests that those who perceive disability discrimination are less likely to seek healthcare.…”
Section: Discussionmentioning
confidence: 99%